A Dyadic Perspective on Speech Accommodation and Social Connection: Both Partners' Rejection Sensitivity Matters. Issue 2 (12th January 2015) - Aguilar, Lauren; Downey, Geraldine; Krauss, Robert; Pardo, Jennifer; Lane, Sean; Bolger, Niall
Abstract: Findings from confederate paradigms predict that mimicry is an adaptive route to social connection for rejection‐sensitive individuals (Lakin, Chartrand, & Arkin, 2008). However, dyadic perspectives predict that whether mimicry leads to perceived connection depends on the rejection sensitivity (RS) of both partners in an interaction. We investigated these predictions in 50 college women who completed a dyadic cooperative task in which members were matched or mismatched in being dispositionally high or low in RS. We used a psycholinguistics paradigm to assess, through independent listeners' judgments ( N = 162), how much interacting individuals accommodate phonetic aspects of their speech toward each other. Results confirmed predictions from confederate paradigms in matched RS dyads. However, mismatched dyads showed an asymmetry in levels of accommodation and perceived connection: Those high in RS accommodated more than their low‐RS partner but emerged feeling less connected. Mediational analyses indicated that low‐RS individuals' nonaccommodation in mismatched dyads helped explain their high‐RS partners' relatively low perceived connection to them. Establishing whether mimicry is an adaptive route to social connection requires analyzing mimicry as a dyadic process influenced by the needs of each dyad member.